Effect of Fu’s subcutaneous needling for cancer pain management: protocol for a pragmatic randomised controlled trial - Yang Cao; Yihan He; Jian Sun; Danghan Xu; Zhanbo Yu; Ximin Cai; Jietao Lin; Tengjiao Lin; Zhaoxi Liu (BMJ Open)
Introduction Pain is a common symptom in patients with cancer, and pain management is crucial for these patients. Fu’s subcutaneous needling (FSN) is a modern acupuncture therapy based on basic medicine commonly used in patients with pain. However, evidence of its effectiveness in treating cancer pain has not been systematically proven. Therefore, this pragmatic randomised controlled trial aims to evaluate the effectiveness and safety of FSN for cancer pain management.Methods and analysis Overall, 120 eligible patients will be recruited and randomly assigned into two groups using block randomisation. Both groups will be administered analgesic drugs according to the National Comprehensive Cancer Network guidelines. The treatment group will receive FSN therapy one time a day for 6 days. Additionally, we will assess analgesic consumption as the primary outcome and the Numerical Rating Scale, outbreak pain, symptom assessment and adverse events as secondary outcomes to evaluate the effect and safety of FSN in treating cancer pain. The incidence of adverse events will be monitored to assess the safety of FSN.Ethics and dissemination Ethics approval was obtained from the Ethics Committee of the First Affiliated Hospital of Guangzhou University of Chinese Medicine (approval No: K(2021)096). The results will be published in a peer-reviewed journal, and trial participants will be informed via email and/or phone calls.Trial registration number ChiCTR2200056348.